Does the corn leafhopper Dalbulus maidis (DeLong & Wolcott) (Hemiptera: Cicadellidae) reproduce in hosts other than maize? - Istchuk, Ademar Novais; da Silva, Paulo Roberto; Borges, Adomiro Roberto Pereira; Neves, Taline Campos Nunes das; Ramos Pereira, Renata; Schwertner, Matheus Henrique; Ishizuka, Tamylin Kaori; Pietrowski, Vanda (EntomoBrasilis, 2023)
The corn leafhopper Dalbulus maidis (DeLong & Wolcott) (Hemiptera: Cicadellidae) is a specialist insect vector of the corn stunting disease complex. This leafhopper has been reported from different overwintering plants, and more information is required regarding other potential Brazilian plants that may serve as reproductive hosts for this specie. The present study aimed to evaluate possible plants for leafhopper reproduction usually found near the maize fields and the D. maidis reproductive differences among maize genotypes. Three trials were conducted to assess D. maidis survival and oviposition on different maize genotypes and other potential host plants. Survival, nymph presence, oviposition, and nymph eclosion rates were observed. No nymphs were observed in plants other than maize. The number of D. maidis adults was influenced by the different maize inbreds, and the mean number of laid eggs varied across the tested maize materials. Oviposition and nymph emergence was observed in pearl millet [Pennisetum glaucum (L.) R. Br., Poaceae] when D. maidis adults were offered only this plant as substrate, although significantly lower than those recorded on maize. Our results suggest that eliminating maize plants in the off-season could be used as a tool to reduce D. maidis reproduction, thereby minimizing the vector population size in the following season.